Detailed resolution analysis reveals spatial T cell heterogeneity in the invasive margin of colorectal cancer liver metastases associated with improved survival. (4th March 2017) - Berthel, Anna; Zoernig, Inka; Valous, Nektarios A.; Kahlert, Christoph; Klupp, Fee; Ulrich, Alexis; Weitz, Juergen; Jaeger, Dirk; Halama, Niels
ABSTRACT: On a broader scale, T cell density and localization in colorectal cancer liver metastases have prognostic and predictive implications. As T cell distribution at higher resolutions has not been fully investigated, a detailed resolution analysis of T cell distribution was performed. Patient tissues were divided into 10 µm distance classes between the tumor border and adjacent normal liver. Thereby, distinct density patterns of T cell localization in relation to the malignant tissue could be detected. At a distance of 20 to 30 µm to the tumor, a decrease of CD3 T cells is common. Within this area, cytotoxic Granzyme B and CD8 + T cells were found to be significantly reduced as well as CD163 macrophages were increased and identified to be in close contact with T cells. Our data suggests a physical or functional border within this region. Survival analysis revealed improved overall survival in patients with high T cells numbers at the direct tumor border. Interestingly, the decreased T cells in the 20 to 30 µm region were also found to be significantly associated with improved survival. Consequently, the detailed localization of T cells, despite blockade, could be associated with improved clinical outcome. The high-resolution analysis represents new insights into relevant heterogenous T cell distributions especially related to clinical responses. As the paradoxical observation of localization-dependent prognostic relevance of T cell densities is only detectable by detailed spatial analyses, this investigation of spatial profiles at higher resolutions is suggested as a new biomarker for survival and response to therapies.